2013
DOI: 10.1371/journal.pone.0082925
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortex Processes Variation in Our Own Speech

Abstract: As we talk, we unconsciously adjust our speech to ensure it sounds the way we intend it to sound. However, because speech production involves complex motor planning and execution, no two utterances of the same sound will be exactly the same. Here, we show that auditory cortex is sensitive to natural variations in self-produced speech from utterance to utterance. We recorded event-related potentials (ERPs) from ninety-nine subjects while they uttered “ah” and while they listened to those speech sounds played ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…Therefore, this system allows for the differentiation between self-generated and external stimulation Ford & Mathalon, 2004;Ford et al, 2007;Heinks-Maldonado et al, 2005;HeinksMaldonado et al, 2007). On the contrary, if the voice feedback and the predicted sensory consequences do not match, an error signal is generated, and hence auditory cortical suppression is reduced (i.e., auditory activity is increased; Behroozmand, Karvelis, Liu, & Larson, 2009;Eliades & Wang, 2008;Heinks-Maldonado et al, 2005;Heinks-Maldonado et al, 2007;Sitek et al, 2013). Complementing these studies, recent evidence (Tian & Poeppel, 2013 has shown that the operation of the internal feedforward system is not an Bartifact^of overt vocal production, since it operates during articulation imagery.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, this system allows for the differentiation between self-generated and external stimulation Ford & Mathalon, 2004;Ford et al, 2007;Heinks-Maldonado et al, 2005;HeinksMaldonado et al, 2007). On the contrary, if the voice feedback and the predicted sensory consequences do not match, an error signal is generated, and hence auditory cortical suppression is reduced (i.e., auditory activity is increased; Behroozmand, Karvelis, Liu, & Larson, 2009;Eliades & Wang, 2008;Heinks-Maldonado et al, 2005;Heinks-Maldonado et al, 2007;Sitek et al, 2013). Complementing these studies, recent evidence (Tian & Poeppel, 2013 has shown that the operation of the internal feedforward system is not an Bartifact^of overt vocal production, since it operates during articulation imagery.…”
mentioning
confidence: 99%
“…These studies have found an N1 amplitude suppression effect during vocal production when compared with the condition of passively listening to prerecorded self-generated voice stimuli Curio, Neuloh, Numminen, Jousmaki, & Hari, 2000;Ford & Mathalon, 2004Ford et al, 2001;Ford et al, 2002;Ford et al, 2007;HeinksMaldonado, Mathalon, Gray, & Ford, 2005;HeinksMaldonado et al, 2007;Houde, Nagarajan, Sekihara, & Merzenich, 2002;H. Liu et al, 2011;Numminen, Salmelin, & Hari, 1999;Sitek et al, 2013;Timm, SanMiguel, Saupe, & Schröger, 2013;Ventura, Nagarajan, & Houde, 2009). Moreover, when participants receive altered self-generated voice feedback, the N1 attenuation effect is smaller than when they listen to intact voice feedback Ford & Mathalon, 2004Ford et al, 2001;Ford et al, 2007;Heinks-Maldonado et al, 2005;HeinksMaldonado et al, 2007;Sitek et al, 2013;Timm et al, 2013).…”
mentioning
confidence: 99%
See 3 more Smart Citations